2020
DOI: 10.1093/jbcr/iraa084
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Burn Injuries in Saudi Arabia: A Systematic Review

Abstract: Burns are potentially catastrophic injuries that disproportionately affect non-Western countries. We summarize results on the epidemiology of burn injuries in Saudi Arabia of all eligible papers through 2019, specifically evaluating the age and gender of patients, the location and mechanism of injury, burn size and severity, and outcomes. Between July 5 and July 10, 2019, a comprehensive literature review was performed on MEDLINE, EMBASE, Google Scholar, and the Cochrane Library. For this search, “Saudi Arabia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…The present study indicated that electrical burns were reported in 1.8% and chemical burns in 1.6%. Almarghoub et al [ 14 ], in a systematic review that summarized results on the epidemiology of burn injuries in Saudi Arabia, reported that Scald injuries (hot water or steam) accounted for 62.4% of injuries, followed by flame-induced burns (28.7%), electrical burns (3.3%), and chemical burns (2.8%). Almost 60% were second-degree burns.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicated that electrical burns were reported in 1.8% and chemical burns in 1.6%. Almarghoub et al [ 14 ], in a systematic review that summarized results on the epidemiology of burn injuries in Saudi Arabia, reported that Scald injuries (hot water or steam) accounted for 62.4% of injuries, followed by flame-induced burns (28.7%), electrical burns (3.3%), and chemical burns (2.8%). Almost 60% were second-degree burns.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding reports by WHO, the annual worldwide incidence of burn injuries in all types was estimated at 11 million burns, of which 180,000 were fatal 4 . Although the majority of burn injuries are caused by hot liquids or fire, they can be raised by cold, friction, radiation, and electric or chemical sources 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The major predictors of morbidity and mortality of burns include age as well as total body surface area (TBSA) of burns [ 1 , 4 ]. In Saudi Arabia, a systemic review was conducted and found that 80-100% of burns are estimated to be less than 40% TBSA [ 5 ]. Furthermore, it is estimated that burns of TBSA more than 40% are associated with major morbidity and mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%